Fragmented Identity and Radicalization in Bhutto’s The Runaways - Rashid, Muhammad; Akram, Sadia; Saad, Manail (sourcecoder, 2025)
The objective of this study is to explore identity crisis and its correlation with the process of radicalization in Fatima Bhutto’s The Runaways. The research closely examines how characters in the narrative navigate and grapple with elements of their identities that are fragmented or in a state of flux. The state of alienation, poverty, and social anxiety emerges as crucial in contributing to radicalization within a society. Bauman’s (2000) theory of liquid modernity works as theoretical framework which is central in understanding radical tendencies of the characters and individuals in the novel. The analysis of the selected text concludes that the individuals suffer from identity crisis while encountering poverty, social frustration and isolation. The findings of the study indicate that individuals suffer due to material concerns, social exclusion and divisions, alienation, internal emptiness and lack of belonging that lead them to identity crisis, fragmentation and radical tendencies.